2017
DOI: 10.3389/fnmol.2017.00027
|View full text |Cite
|
Sign up to set email alerts
|

Rpph1 Upregulates CDC42 Expression and Promotes Hippocampal Neuron Dendritic Spine Formation by Competing with miR-330-5p

Abstract: Alzheimer’s disease (AD) is a heterogeneous neurodegenerative disease. Recent studies employing microRNA-seq and genome-wide sequencing have identified some non-coding RNAs that are influentially involved in AD pathogenesis. Non-coding RNAs can compete with other endogenous RNAs by microRNA response elements (MREs) and manipulate biological processes, such as tumorigenesis. However, only a few non-coding RNAs have been reported in the pathogenesis of AD. In this study, we constructed the first competing endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 64 publications
3
56
0
Order By: Relevance
“…To activate the Cre enzyme, postnatal day (P)1 or P3 mice were injected with tamoxifen (Sigma) intraperitoneally (I.P.) (1.5 mg/25 g body weight for Sox2-CreER mice, 3.5 mg/25 g body weight for Lgr5-CreER mice, and 2 mg/25 g body weight for Sox9-CreER mice, which were all consistent with previous reports [4,73,74]). For each experiment, the control mice were also injected with the same amount of tamoxifen.…”
Section: In Vivo Ckd Of Foxg1 In Sox2+ Scs Sox9+ Scs and Lgr5+ Progsupporting
confidence: 78%
See 1 more Smart Citation
“…To activate the Cre enzyme, postnatal day (P)1 or P3 mice were injected with tamoxifen (Sigma) intraperitoneally (I.P.) (1.5 mg/25 g body weight for Sox2-CreER mice, 3.5 mg/25 g body weight for Lgr5-CreER mice, and 2 mg/25 g body weight for Sox9-CreER mice, which were all consistent with previous reports [4,73,74]). For each experiment, the control mice were also injected with the same amount of tamoxifen.…”
Section: In Vivo Ckd Of Foxg1 In Sox2+ Scs Sox9+ Scs and Lgr5+ Progsupporting
confidence: 78%
“…The Foxg1-floxp mice were a gift from Prof. Chunjie Zhao from Southeast University [24]. Sox9-IRES-CreER mice were a gift from Prof. Fengchao Wang from the National Institute of Biological Sciences (NIBS), Beijing [73]. We performed all animal procedures according to protocols that were approved by the Animal Care and Use Committee of Southeast University and that were consistent with the National Institute of Health's Guide for the Care and Use of Laboratory Animals.…”
Section: Animalsmentioning
confidence: 99%
“…Interestingly, the occurrence in neurons has been described for the miRNAs miR-330 (14) and miR574 (49) and some miRNAs of the let-7 family (58,60,74,94,101).…”
Section: Six Mirnas Show Stronger Upregulation In Gm Lesions Than In mentioning
confidence: 99%
“…RPPH1 is a well-known RNA subunit of RNase P, which is responsible for tRNA maturation in all three domains of life [ 17 ]. A previous study demonstrated that one of our tested ceRNA pathways, RPPH1 /miR-330-5p/CDC42, may be involved in the compensatory behaviour of brain neurons to combat synaptic loss during AD pathogenesis [ 18 ]. However, the downstream pathway in breast cancer is currently not known.…”
Section: Discussionmentioning
confidence: 99%